Anti‐proliferative and apoptotic activities of constituents of chloroform extract of Juglans regia leaves - Salimi, M. (Cell Prolif, 2014)
OBJECTIVES: To evaluate anti‐proliferative as well as apoptotic activities of compounds identified in chloroform extract of Juglans regia leaves, on human breast and oral cancer cell lines (MCF‐7 and BHY). MATERIALS AND METHODS: Column chromatography, MTT assay, flowcytometry and western blotting have all been used in the study. RESULTS: Bioassay‐guided fractionation of chloroform extract of J. regia afforded isolation of 5‐hydroxy‐3,7,4′‐trimethoxyflavone [1], lupeol [2], daucosterol [3], 4‐hydroxy‐α‐tetralone [4], β‐sitosterol [5], 5,7‐ dihydroxy‐3,4′‐dimethoxyflavone [6] and regiolone [7]. Structures of the compounds were established on the basis of spectroscopic analyses [Nuclear magnetic resonance (NMR) and mass]. All compounds inhibited proliferation of MCF‐7 (human breast adenocarcinoma) and BHY (human oral squamous carcinoma) cells in a concentration‐dependent manner. Compounds 6 and 7 had potent cytotoxic effects on both MCF‐7 and BHY cells (IC (50) 21–51 μm), yet were not toxic to normal cells. MCF‐7 growth inhibition was attributed to apoptosis; population of apoptotic cells increased from 1.12% in controls to 5.64 and 8.1% after 48‐h treatment with compounds 6 and 7, indicating their potential at inducing early and late apoptosis. The caspase cascade was not activated, as indicated by only insignificant cleavage of caspase‐3. CONCLUSIONS: Our results suggest that compounds 6 and 7 can induce apoptosis in MCF‐7 cells through the caspase‐3 independent pathway.